2010
DOI: 10.3892/ijmm_00000350
|View full text |Cite
|
Sign up to set email alerts
|

The combination of exercise training and α-lipoic acid treatment has therapeutic effects on the pathogenic phenotypes of Alzheimer's disease in NSE/APPsw-transgenic mice

Abstract: Abstract. Exercise training was suggested as a practical therapeutic strategy for human subjects suffering from Alzheimer's disease (AD) in our previous study. Therefore, the purpose of this study was to investigate the effects of combining exercise training with the administration of antioxidants on the pathological phenotype of AD. To accomplish this, non-transgenic mice (Non-Tg) and NSE/ APPsw Tg mice were treated with ·-lipoic acid and treadmill exercised for 16 weeks, after which their brains were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 43 publications
2
38
0
2
Order By: Relevance
“…[52] suggested that neuroprotective by Akt may be regulated through downstream factor of HSP-70 expression, indicating that deficiency of HSP70 is possibly caused by the Aβ-induced down-regulation of Akt protein. The present study showed that the level of HSP70 was decreased in the cortex of Tg mice compared to non Tg mice; however, treadmill exercise could increase HSP70 protein which is in accordance with previous study [27,37,38]. Therefore, these results demonstrated that the activation of PI3-K/Akt signaling and HSP70 might ameliorate the cognitive dysfunction in the cortex of AD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[52] suggested that neuroprotective by Akt may be regulated through downstream factor of HSP-70 expression, indicating that deficiency of HSP70 is possibly caused by the Aβ-induced down-regulation of Akt protein. The present study showed that the level of HSP70 was decreased in the cortex of Tg mice compared to non Tg mice; however, treadmill exercise could increase HSP70 protein which is in accordance with previous study [27,37,38]. Therefore, these results demonstrated that the activation of PI3-K/Akt signaling and HSP70 might ameliorate the cognitive dysfunction in the cortex of AD.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, caspase-3, a pro-apoptosis factor, is activated during the last step of apoptosis and could be decreased by the Bcl-2 and increased by the Bax protein [36]. We found that the level of caspase-3 proteins were increased in the cortex of Tg mice compared to non-Tg mice while treadmill exercise induced down-regulation of the caspase-3 in the cortex of Tg mice, which was consistent with previous reports [27,37,38]. Furthermore, cyclooxygenase-2 (COX-2) contributes to synaptic plasticity and memory function whereas when overexpressed it has been associate with neurotoxicity in AD [39].…”
Section: Discussionsupporting
confidence: 92%
“…Disappointingly, there is no evidence that NSAIDs have any effect in changing disease progression, and their use may actually be detrimental (Willard et al 2000;Moore and O'Banion 2002;Martin et al 2008;Wolfson et al 2002). Several compounds with anti-oxidative properties, such as vitamin E, alpha lipoic acid and resveratrol are also being investigated for effectiveness in slowing the progression of AD, but there has been no conclusive evidence of benefit (Granzotto and Zatta 2011;Isaac et al 2008;Cho et al 2010).…”
Section: Drugs In Trialmentioning
confidence: 95%
“…Neuroscience 301 (2015) [480][481][482][483][484][485][486][487][488][489][490][491][492][493][494][495] expression/activation of several pro-apoptotic proteins (Cho et al, 2010;Um et al, 2011) and increased mitochondrial biogenesis (Steiner et al, 2011) and antioxidant capacity (Camiletti-Moiron et al, 2013). However, other still unknown mitochondrial-mediated mechanisms may also be involved, contributing to the improved functional phenotype associated with exercise.…”
Section: Introductionmentioning
confidence: 99%